Increased airway resistance can be related to the decrease in the functional capacity in obese women - Perossi, Larissa; Holtz, Mayara; Santos, Daniele Oliveira dos; Perossi, Jéssica; Souza, Hugo Celso Dutra de; Salgado Junior, Wilson; Gastaldi, Ada Clarice (PLOS ONE, 2022)
Background and objective Obesity can increase the airways resistance, mainly in the periphery, leading to dyspnea perception that can impair the functional capacity. This study aimed to analyze if airways resistance could be related to the walking capacity of women with morbid obesity. Methods Thirty-seven women with grade III obesity in preoperative bariatric surgery were evaluated using the spirometry test, impulse oscillometry system (IOS), and six-minute walk test (6MWT). Additionally, data about their daily dyspnea perception and physical activity level were collected. Results Variables of the spirometry test did not detect ventilator disorders. Compared to the predicted values, the IOS identified significant increase in airways resistance (kPa/L/s) (R5: 0.36 (0.34; 0.36) and 0.53 (0.47; 0.61); R20: 0.30 (0.28; 0.30) and 0.41 (0.35; 0.45); R5-20: 0.06 (0.06; 0.06) and 0.14 (0.10; 0.15); X5: -0.03 (-0.04; -0.01) and -0.20 (-0.27; -0.18), respectively). The distance walked in the 6MWT, 491.4±60.4m was significantly correlated to R5 (rho = -0.41, p = 0.01), R5-20 (rho = -0.52, p = 0.001), and X5 (rho = 0.54, p = 0.0006). Conclusion The IOS is able to identify changes in airway resistance even before the onset of symptoms. When evaluated by IOS women with severe obesity and normal spirometry exhibited central and peripheral airways obstruction. The correlations between the IOS and six-minute walk distance suggest that increased peripheral airways resistance could be related to worsening functional capacity.